Microspore Morphology of Isoetes Species (Lycophyta) from Southern South America - Macluf, Carmen Cecilia (2006)
Microspores of the 24 species of Isoetes that grow in southern South America were analyzed under a light microscope and scanning electron microscope. The microspores are monolete, elliptic in polar view, 30–40 µm long, and 20–25 µm wide. A background with various characteristics is seen on each surface. A supra-laesural expansion is present. The perispore is ornamented and has a perforated background. In section, it has a lacunose structure. The exospore is smooth, and it has a compact structure in section. The studied species could be divided into three groups by their perispore ornamentation: equinate, rugulate, and tuberculate. Microspore size was positively correlated with increasing ploidy level, and larger microspores were associated with terrestrial habitats. A convergence in ornamentation was found between spores produced by the studied species and those that grow in regions outside of the area under study.